Pilot testing of food safety knowledge, attitude and perception towards food handlers' hygiene practice among night market food consumers - Mohammad Jaafar, Normardiana; Jaafar, Siti Nur'afifah; Mahyudin, Nor Ainy (2016)
Recently, food poisoning cases have been increase which has lead to impacts in term of health and economy in developed countries. Despite the current situation, the night market foods still famous among consumers. Street food vendors in night market has been risen in recent years, however this scenario raised public health challenges. The aim of this study is to asses the level of knowledge, attitude and perception on food handlers’ practice among consumers. This research is beneficial in understanding the current situation of food safety knowledge, practice and perception towards food handlers’ practice among consumers besides could be used to improve food safety at night market. At the early stage, pilot test was conducted to test the reliability and validity of the instrument that will be used in the real study. This stage was important to test whether the articulation of the method(s) and instruments selected for use in a research adequate to meet research objectives. The pilot test was conducted at four states in Malaysia; Perak, Perlis, Selangor, Terengganu. A total of 120 consumers were investigated from April to May 2015. By using Cronbach Alpha test, the reliability coefficient test was 0.70 and above. The finalized questionnaire consist of 65 items-knowledge (32), attitude (12), practice (15), familiarity (3), and purchase intention (3). Overall, the articulation of the method and instrument designated was satisfactorily reliable, valid and adequate to be used in a research to assess the level of consumers’ food safety knowledge, consumers’ attitude towards food safety and perception on food handlers’ practice among consumers towards night market foods purchase intention with familiarity with night market foods as moderating factor.